2018
DOI: 10.7717/peerj.5596
|View full text |Cite
|
Sign up to set email alerts
|

Local-scale determinants of arboreal spider beta diversity in a temperate forest: roles of tree architecture, spatial distance, and dispersal capacity

Abstract: Spiders are a functionally important taxon in forest ecosystems, but the determinants of arboreal spider beta diversity are poorly understood at the local scale. We examined spider assemblages in 324 European beech (Fagus sylvatica) trees of varying sizes across three forest stands in Würzburg (Germany) to disentangle the roles of tree architecture, spatial distance, and dispersal capacity on spider turnover across individual trees. A large proportion of tree pairs (66%) showed higher compositional dissimilari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Gómez et al (2016) showed that the density of spiders building aerial webs increases with increasing vegetation height and the number of vegetation layers. Zhang et al (2018) showed that spider communities living on the European beech Fagus sylvatica are significantly affected by such parameters of trees as trunk diameter at breast height, canopy volume, and foliage cover.…”
Section: Introductionmentioning
confidence: 99%
“…Gómez et al (2016) showed that the density of spiders building aerial webs increases with increasing vegetation height and the number of vegetation layers. Zhang et al (2018) showed that spider communities living on the European beech Fagus sylvatica are significantly affected by such parameters of trees as trunk diameter at breast height, canopy volume, and foliage cover.…”
Section: Introductionmentioning
confidence: 99%
“…Porrhomma pygmaeum was the most abundant spider species in both alder carr plots (Table 1). The lowest number of species was found in the managed oak-lime-hornbeam forest (11) and the highest in primeval alder carr (23 species). However, the calculated estimators indicated higher species richness (varying depending on the estimator), especially for primeval alder carr, for which the sampling completeness was the lowest, at 53%, whereas in the other plots sampling completeness was about 70-80% (Table 2).…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, the collected material derives not only from the foliage growing out of thin branches but also from tree trunks. As a result, spiders from these two microhabitats have previously been analyzed as one group [9][10][11], which might have led to incorrect conclusions as these two habitats are markedly different in terms of microhabitat structure and microclimatic conditions, and thus spider assemblages inhabiting them are likely to be different [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…geographic distances; spatial eigenvectors) (Carvalho et al ., ). In relation to spider metacommunity structure, most studies found that species‐sorting assembly processes predominate over dispersal limitation to spider metacommunity structure, as most studies detected a higher relative importance of environmental over spatial predictors in explaining the variation in spider composition across a diverse array of environments, including dunes, forests and grasslands (Baldissera et al ., , ; Jiménez‐Valverde & Lobo, ; Jiménez‐Valverde et al ., ; Carvalho et al, 2012a, 2012b; Rodriguez‐Artigas et al ., ; Tonkin et al ., ; Zhang et al ., ). In fact, many authors have found weaker influence of geographic distances on spider assemblage composition compared with environmental predictors (Jiménez‐Valverde et al ., ; Carvalho et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, several studies investigating the relative importance of environmental drivers and spatial predictors have been conducted recently. In general, most studies have detected a prevailing importance of environmental over spatial predictors, suggesting that spider assemblages are mostly structured by species sorting (Baldissera et al ., ; Carvalho et al ., ; Rodriguez‐Artigas et al ., ; Zhang et al ., ), although the contribution of environmental drivers seems to change with the spatial extent of a study (Carvalho et al ., ).…”
Section: Introductionmentioning
confidence: 99%